Remoção de 17α-etinilestradiol por meio de fotocatálise em reator de leito fluidizado - Martins, Fernanda Lisboa (2017)
This work compared the efficiency of removing the 17-α-ethynylestradiol (EE2) through advanced oxidative processes (POA) and granular activated carbon adsorption (CAG). EE2 is a synthetic female hormone common in domestic sewage and effluent from pharmaceutical industries. This hormone is a type of emerging pollutant that causes endocrine disruption in living beings even in concentrations of nanograms order. The EE2 removal was analyzed in a prototype of a 10 L reactor, with upward flow CAG fluidized bed, using four lamps emitting ultraviolet radiation, with batch time of 2 hours in each process. Photolysis showed 5% of efficiency, while photocatalysis removed 87% of EE2. The adsorption processes in CAG and titanium dioxide immobilized at CAG removed 82 and 89%, respectively.